Water relations, gas exchange, and growth of resprouts and mature plant shoots of Arbutus unedo L. and Quercus ilex L. (Oecologia, 1994)
Resprout and mature plant shoot growth, leaf water status and gas exchange behavior, tissue nutrient content, flowering, and production were studied for co- occurring shallow-rooted (Arbutus unedo L.) and deep- rooted (Quercus ilex L.) Mediterranean tree species at the Collserola Natural Park in Northeast Spain. Resprouts showed higher growth rates than mature plant shoots. During fall, no differences in eco-physiological perfor- mance of leaves were found, but mobilization of carbo- hydrates from burls strongly stimulated growth of fall re- sprouts compared to spring resprouts, despite low expo- sed leaf area of the fall shoots. During summer drought, resprouts exhibited improved water status and carbon fixation compared to mature plant shoots. Shoot growth of Q. iIex was apparently extended due to deep rooting so that initial slower growth during spring and early summer as compared to A. unedo was compensated. Tis- sue nutrient contents varied only slightly and are postula- ted to be of minor importance in controlling rate of shoot growth, perhaps due to the relatively fertile soil of the site. Fall flowering appeared to inhibit fall shoot growth in A. unedo, but did not occur in Q. ilex. The results de- monstrate that comparative examinations utilizing vege- tation elements with differing morphological and physio- logical adaptations can be used to analyze relatively complex phenomena related to resprouting behavior. The studies provide an important multi-dimensional back- ground framework for further studies of resprouting in the European Mediterranean region.